The Correlation Study among EFL Learners’ Reticence, Motivation and Speaking Habit - Lalu Wahyu Wiranata; Selamet Riadi Jaelani; Siti Maysuroh (Humanitatis : Journal of Language and Literature, 2023)
This research aims to investigate the correlation between students' reticence, motivation, and their speaking habits which effected their speaking skills. The method used is a quantitative approach with a correlational design. The population was the eleventh-grade students of MA NW Montong Kubur comprising one class with a total of 35 students. The researcher used the total sampling method, in which all eleventh-grade students became respondents. Data collection was done through questionnaire and speaking test. The results showed that the correlation coefficient between students' speaking anxiety and their speaking achievement was r=0.312. Although these two variables have a negative correlation, the value of r=0.312 can still be classified as a significant correlation. Furthermore, the correlation coefficient between students' motivation and their speaking habits was found to be r=0.032. This means that there is a positive relationship between these variables, but the value of r=0.032 indicates a low correlation. Finally, the results showed that the correlation coefficient between students' speaking reticence, motivation, and speaking habits was r=0.105 which means that these three variables have a positive correlation, although the value of 0.105 indicates a very low level of correlation.